A Rare Case of Primary Cardiac T-cell Lymphoma in Immunocompetent Adult. (9th November 2022) - Chen, J; Jetly, R; Connor, E
Abstract: Introduction/Objective: Primary cardiac lymphoma (PCL) is an extranodal lymphoma involving only the heart and/or the pericardium. It is exceedingly rare, accounting for <2% of primary cardiac neoplasms in a surgical series and 0.05% of a >12, 000 autopsies' series, and is often associated with an immunocompromised state. Most PCL are of B- cell lineage with T-cell lymphoma constituting < 10%. Methods/Case Report: We report a case of unexpected sudden death due to primary cardiac T-cell lymphoma in a 48-year-old immunocompetent man without significant medical history who presented in cardiopulmonary arrest following a two-week history of cold-like symptoms. Autopsy revealed an irregular, discontinuous tan plaque on the epicardial surface that extended over the right and left ventricles, and sectioning revealed that extension of the lesion throughout the subvalvular myocardium of the left ventricular wall, interventricular septum, and medial aspects of the right ventricle. The lesion had irregular areas of necrosis and hemorrhage. No lymphadenopathy or other visceral lesions were identified. Histologically, the myocardium had a regionally necrotic, angiocentric infiltrate of atypical, large, pleomorphic lymphoid cells with large, irregular nuclei, vesicular chromatin, and conspicuous nucleoli. Initial immunohistochemical work-up showed a profile of CD45+/CD20-/CD3+ suggesting a T-cell origin with CD8 predominance (CD4-/CD8+). Further work-up demonstrated a profile as CD2+/CD7+/CD25+/CD30+/EBV(EBER- ISH)+/Ki67(70-80%)/ and ALK-1-/BCL6-/CD5-/CD10-/CD56-, supporting extranodal NK/T-cell lymphoma, extranasal type with a cytotoxic T-cell subtype (perforin+/granzyme B+/TIA-1+/TCR Beta F1+). Results (if a Case Study enter NA): NA. Conclusion: Primary cardiac lymphoma with cytotoxic T-cell subtype is extremely rare and fatal. This case is the third report over the past two decades, to our knowledge, of a primary cardiac T-cell lymphoma leading to acute heart failure and sudden death in an immunocompetent adult.